Analysis of genetic polymorphisms associated with intervertebral disc degeneration - Kitis, Serkan; Coskun, Zeynep Mine; Tasdemir, Pelin; Tuncez, Ebru; Zamani, Ayse Gul; Acar, Aynur (Cellular and Molecular Biology, 2018)
Intervertebral disc degeneration (IVDD) is a common degenerative spinal condition. Recent studies have shown that the incidence of disc herniation and disc degeneration may be explained by genetic factors.  In this study, we investigated the link between various polymorphic variants of the vitamin D receptor (VDR), matrix metalloproteinase 2 (MMP2), and insulin like growth factor 1 receptor (IGF1R) genes and IVDD in patients with IVDD, in Turkey. We examined and genotyped 199 patients with IVDD and 197 healthy individuals. Genomic DNA was isolated from the peripheral blood leukocytes of all participants, and analyzed using real-time PCR. Via melting curve analysis, VDR, MMP2, and IGF1R polymorphism variant distributions were determined. The patients with IVDD showed higher frequencies of the VDR ApaI A allele genotype as compared to the control group; however, there were no significant differences in the frequencies or allelic distributions of the IGF1R and MMP2 genotypes between the IVDD patients and the control group. The incidence of IVDD in these Turkish patients is correlated with the VDR ApaI gene polymorphism, but not with the IGF1R and MMP2 polymorphisms.